Eksistensi Lahan Pasang Surut Untuk Pertanian Di Desa Mulya Sari Kabupaten Banyuasin - Helfa Septinar; Ita Emilia; Yunita Panca Putri; Eva Suryani (Universitas PGRI Palembang, 2023)
Tidal land is land that is in a zone where it is still influenced by sea tides. This land is marginal and can still be developed while maintaining water availability and pyrite oxidation. In Sumatra, Kalimantan and Irian Jaya, tidal land has been opened through the transmigration program. This land was opened as agricultural land to meet the food needs of the community. One of the efforts in managing tidal land is water management. This research aims to determine the existence of tidal land as agricultural land in Mulya Sari village. The method used is field observation, data collection through direct interviews and related literature, and descriptive analysis. The results of the research show that for the existence of tidal land, the community in Mulya Sari village optimizes the channels built by orders and also those created by the community itself. The water conditioning in each plot of land and tertiary canals is maintained by the optimal operation of the automatic water gates. In addition, the water level must be above the ground water level to prevent oxidation of the pyrite layer. Under these conditions, the tidal land in Mulya Sari village continues to exist as agricultural land. Tidal land is land that is in a zone where it is still influenced by sea tides. This land is marginal and can still be developed while maintaining water availability and pyrite oxidation. In Sumatra, Kalimantan and Irian Jaya, tidal land has been opened through the transmigration program. This land was opened as agricultural land to meet the food needs of the community. One of the efforts in managing tidal land is water management. This research aims to determine the existence of tidal land as agricultural land in Mulya Sari village. The method used is field observation, data collection through direct interviews and related literature, and descriptive analysis. The results of the research show that for the existence of tidal land, the community in Mulya Sari village optimizes the channels built by orders and also those created by the community itself. The water conditioning in each plot of land and tertiary canals is maintained by the optimal operation of the automatic water gates. In addition, the water level must be above the ground water level to prevent oxidation of the pyrite layer. Under these conditions, the tidal land in Mulya Sari village continues to exist as agricultural land.